Prevalence and Antimicrobial Resistance of Mycoplasma genitalium Infection Among Women Living With Human Immunodeficiency Virus in South Africa: A Prospective Cohort Study. (29th January 2019) - Ong, Jason J; Magooa, Mahlape Precious; Chikandiwa, Admire; Kelly, Helen; Didelot, Marie-Noelle; Muller, Etienne E; Maseko, Venessa; Segondy, Michel; Delany-Moretlwe, Sinead; Kularatne, Ranmini; Mayaud, Philippe; ,
Abstract: This prospective cohort study of 622 women living with human immunodeficiency virus (HIV) from Johannesburg (2012) detected Mycoplasma genitalium in 7.4% (95% confidence interval [CI]: 5.5–9.7, 46/622), with detection more likely with lower CD4 counts(adjusted odds ratio [AOR] 1.02 per 10 cells/μL decrease, 95% CI: 1.00–1.03) and higher plasma HIV-1 RNA (AOR 1.15 per log copies/mL increase, 95% CI: 1.03–1.27). No mutations for macrolide/quinolone resistance was detected.